2010
DOI: 10.1063/1.3449557
|View full text |Cite
|
Sign up to set email alerts
|

Low efficiency droop in blue-green m-plane InGaN/GaN light emitting diodes

Abstract: We investigated the electroluminescence and relatively external quantum efficiency (EQE) of m-plane InGaN/GaN light emitting diodes (LEDs) emitting at 480 nm to elucidate the droop behaviors in nitride-based LEDs. With increasing the injection current density to 100 A/cm2, the m-plane LEDs exhibit only 13% efficiency droop, whereas conventional c-plane LEDs suffer from efficiency droop at very low injection current density and the EQE of c-plane LEDs decrease to as little as 50% of its maximum value. Our simul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
108
0
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(114 citation statements)
references
References 11 publications
4
108
0
2
Order By: Relevance
“…Several groups have linked this behaviour directly to the absence of the internal electric fields. From measurements on non-polar LEDs, Ling et al 18 and Li et al 19 assigned the reduction in droop to reduced losses associated with carrier spill over due to the improved carrier confinement. However, an alternative explanation was put forward by Li et al 20 and Chang et al 21 who suggested that droop was reduced because of the improvement in hole distribution amongst the QWs in multiple QW LEDs.…”
mentioning
confidence: 99%
“…Several groups have linked this behaviour directly to the absence of the internal electric fields. From measurements on non-polar LEDs, Ling et al 18 and Li et al 19 assigned the reduction in droop to reduced losses associated with carrier spill over due to the improved carrier confinement. However, an alternative explanation was put forward by Li et al 20 and Chang et al 21 who suggested that droop was reduced because of the improvement in hole distribution amongst the QWs in multiple QW LEDs.…”
mentioning
confidence: 99%
“…One way to reduce the QCSE is to suppress the polarization by growing the InGaN/GaN LEDs along those nonpolar or semipolar orientations. [8][9][10][11] Even in LEDs grown along [0001] orientation, the polarization in the InGaN/GaN MQWs can be suppressed by embedding the InGaN quantum well between the polarization matched quaternary AlInGaN quantum barriers. 12 Apart from the above methods, the polarization induced electric field within the quantum wells can be screened by Si doping the quantum barriers.…”
mentioning
confidence: 99%
“…[19][20][21] Upon raising the current density to a level of 100 A/cm 2 , efficiency droop has been significantly reduced from 50% with polar QWs to 13% in nonpolar QWs. 21 Understanding the mechanism of the residual droop in nonpolar LEDs will be instrumental towards droop-free LED devices.…”
mentioning
confidence: 99%
“…13,14 Some of these factors have been found to be tightly associated with the internal polarization field. [15][16][17][18][19][20][21] The reduction on internal polarization and the increase of hole concentrations in nonpolar QWs can efficiently suppress the loss during carrier injection. [19][20][21] Potentially, the interplay of polarization fields and Auger recombination in nonpolar QWs can be manipulated to optimize the device performance.…”
mentioning
confidence: 99%
See 1 more Smart Citation